2014
DOI: 10.1088/0253-6102/62/3/21
|View full text |Cite
|
Sign up to set email alerts
|

Heat Generation by Electric Current in a Quantum Dot Molecular Coupled to Ferromagnetic Leads

Abstract: We study the properties of the heat flow generated by electric current in a quantum dot (QD) molecular sandwiched between two ferromagnetic leads. The heat is exchanged between the QD and the phonon reservoir coupled to it. We find that when the leads' magnetic moments are in parallel configuration, the total heat generation is independent on the leads' spin-polarization regardless of the magnitude of the intradot Coulomb interaction. This behavior is similar to that of the electronic current. In the antiparal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 39 publications
(22 reference statements)
2
19
0
Order By: Relevance
“…Moreover, the central position of the two peaks move, respectively, toward μ +hω q /2 and −(U +hω q /2) with reduced widths. This non-monotonous variation of the heat generation with, respectively, to the ferromagnetism on the leads has been found in previous work, in which the electrons are driven by the usual electric bias [51].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Moreover, the central position of the two peaks move, respectively, toward μ +hω q /2 and −(U +hω q /2) with reduced widths. This non-monotonous variation of the heat generation with, respectively, to the ferromagnetism on the leads has been found in previous work, in which the electrons are driven by the usual electric bias [51].…”
Section: Resultssupporting
confidence: 80%
“…The dot single-electron Green's functionsG r,a,<,> σ (ω) are the Fourier transforms ofG r,a,<,> σ (t) defined in terms of Hamiltonian (2), i.e., the retarded [50]. By employing the equation of motion technique, the retarded Green's function is obtained as [31,50,51]…”
Section: Model and Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the heat is generated due to the EPI, through which the energy associated with the electric current in central region is transferred to the phonon bath in the form of heat. They demonstrated that the law of the heat generation in macroscopic system, i.e., the Joule law, breaks down in zero-dimensional quantum-dot (QD) system and some unique behaviors of the heat current were predicted [13,14,[20][21][22][23][24][25][26][27]. For example, resonant phonon emitting occurs when the modified intradot Coulomb interaction is equal to the phonon energy, giving rise to a huge peak in heat generation despite a very weak electric current [14].…”
Section: Introductionmentioning
confidence: 99%
“…[29]. It should be noted that the electron spin degree of freedom has not attracted much attention in those previous works concerning heat generation or thermal diode [13,14,[20][21][22][23][24][25][26][27]. Recently, we studied the heat generation in a system composed of a QD connected to ferromagnetic leads, and found that the ferromagnetism of the external leads will influence the heat generation and the electric current in different ways.…”
Section: Introductionmentioning
confidence: 99%